The The Effect of Previous Year's Audit Opinion, Liquidity and Profitability on Going Concern Audit Opinion - Bhaktiar, R. Enough; Wulandari, Andini (Jurnal Akuntansi Bisnis dan Ekonomi, 2025)
This study aims to determine the effect of the Previous Year's Audit Opinion, Liquidity, and Profitability on the Going Concern Audit Opinion (A case study of Consumer Cyclical Companies listed on the Indonesia Stock Exchange in 2019-2024). The sampling method used in this study was purposive sampling. The samples that used was from Consumer Cyclical Companies during 2019-2024. The data analysis method used was logistic regression analysis using SPSS software. The results of the study stated that the Previous Year's Audit Opinion had a significant effect on the Going Concern Audit Opinion. Meanwhile, Liquidity and Profitability had no effect on the Going Concern Audit Opinion.